Probability Models for Prediction of Annual Maximum Daily Rainfall for Nagpur - Mohanty, S.; Marathe, R.A.; Singh, Shyam (Journal of Soil and Water Conservation, 2022)
The knowledge of one day maximum rainfall is of great importance of hydrological design of structures, planning of soil conservation measures and thereby watershed development. Therefore annual daily rainfall data for 30 years (1996 to 1995) for the station Nagpur has been collected and frequency analysis of maximum daily rainfall has been attempted. The annual maximum daily rainfall data has been fitted to four different Probability distribution function i.e. Normal, Log-Normal, Extreme value Type-I and Log Pearson Type-III distributions and probable rainfall values for different return periods has been estimated. These estimated values have been compared with the values obtained by Weibull's method. The analysis indicates that, the Extreme value Type-I distribution gives the closest fit to the observed data, hence it can be used to predict maximum daily rainfall for higher return periods.